CANCER PATIENT CARE FROM THE PERSPECTIVE OF PRIMARY HEALTH CARE NURSES - Santos, Marisa Gomes dos; Conceição, Vander Monteiro da; Araújo, Jeferson Santos; Biffi, Priscila; Silva, Paola Sabino da; Bitencourt, Julia Valeria de Oliveira Vargas (Cogitare Enfermagem, 2024)
Objective: To describe nurses' perceptions of cancer patient care in Primary Health Care. Method: A qualitative study was conducted in 26 Family Health Centers in a municipality in western Santa Catarina - Brazil, between September and October 2022. A total of 33 nurses took part and completed an online questionnaire. The text was interpreted based on the conceptual precepts of organizational culture from Chiavenatto's administrative theory. The frequency of responses analyzed objective questions; the Collective Subject Discourse was used for the essay questions. Results: Nurses perceive themselves as unprepared and identify a lack of protocols and organizational flows. Final considerations:In primary Health Care, there is a belief consolidated in everyday work and becomes part of the organizational culture of health services, that cancer patients should go on to specialist care. There is a lack of knowledge of health policies, which implicates professionals in caring for cancer patients.